DICK continuum in organizational learning framework - Selamat, Mohamad Hisyam; Mat Samsudin, Mohd Amir (Springer US, 2012)
Klimecki and Lassleben (1998) define organizational learning (OL) as a communication-based process where the organization overcomes its previous boundaries of knowledge and ability by allowing its members to share knowledge, interact, influence each other, and cope with difficult situations.On the other hand, Nonaka and Takeuchi (1995) viewed OL as involving the generation, absorption, and sharing of tacit knowledge, and emphasized the importance of interaction among people toward the development of OL capabilities. In short, OL is the process of continuous innovation through the creation of new knowledge. It is an ongoing process that takes place as staff members engage in knowledge work (Davenport et al. 1998).These views illustrate the importance of having continuous information systems (IS) updates using the medium of communication among the employees. However, to enable t ...